Isocaloric carbohydrate versus carbohydrate-protein ingestion and cycling time-trial performance - Toone, R. J.; Betts, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
This study was designed to compare the effects of energy-matched carbohydrate (CHO) and carbohydrate-protein (CHO-PRO) supplements on cycling time-trial performance. Twelve competitive male cyclists and triathletes each completed 2 trials in a randomized and counterbalanced order that were separated by 5-10 d and applied in a double-blind manner. Participants performed a 45-min variable-intensity exercise protocol on a cycle ergometer while ingesting either a 9% CHO solution or a mixture of 6.8% CHO plus 2.2% protein in volumes providing 22 kJ/kg body mass. Participants were then asked to cycle 6 km in the shortest time possible. Blood glucose and lactate concentrations were measured every 15 min during exercise, along with measures of substrate oxidation via indirect calorimetry, heart rate, and ratings of perceived exertion. Mean time to complete the 6-km time trial was 433 ± 21 s in CHO trials and 438 ± 22 s in CHO-PRO trials, which represents a 0.94% (CI: 0.01, 1.86) decrement in performance with the inclusion of protein (p = .048). However, no other variable measured in this study was significantly different between trials. Reducing the quantity of CHO included in a supplement and replacing it with protein may not represent an effective nutritional strategy when the supplement is ingested during exercise. This may reflect the central ergogenic influence of exogenous CHO during such activity.